UJI BERKELANJUTAN EKOLOGI CACING TANAH Lumbricus rubellus PADA BAHAN INDUK TANAH TAMBANG EMAS DENGAN MEMANFAATKAN KOMPOS - Frengky Kosho; Zetly Estefanus Tamod; Wenny Tilaar (Sam Ratulangi University, 2020)
This study aims to determine the effect of the provision of compost, cow manure and chicken manure on the ecological sustainability of earthworms (Lumbricus rubellus), on gold mine soil parent material; and on the initial growth of upland paddy unsrat variety 1. This research was carried out in May to July 2019 at the Greenhouse of the Faculty of Agriculture, Sam Ratulang University in Manado. The design used in this study used a completely randomized design (CRD) method with 3 treatments and 3 replications. The results showed that the provision of compost, cow manure and chicken manure gave good results on ecological sustainability of earthworms (Lumbricus rubellus), on fertility in gold mine soil parent material, and on early growth of upland paddy unsrat variety 1.*eprm*